Effectiveness, safety, and long-term outcomes of non-powered mechanical sheaths for transvenous lead extraction. Issue 8 (1st August 2017) - Kutarski, Andrzej; Czajkowski, Marek; Pietura, Radosław; Obszański, Bogdan; Polewczyk, Anna; Jacheć, Wojciech; Polewczyk, Maciej; Młynarczyk, Krzysztof; Grabowski, Marcin; Opolski, Grzegorz
Abstract: Aims: To analyse the effectiveness, safety and long-term outcomes of conventional non-powered mechanical systems for transvenous lead extraction (TLE) performed by experienced first operators. Outcomes were assessed according to lead location and type of operating room in which the procedure was performed. Methods and results: Data from 2049 patients (mean age: 65 years), with infectious (40%) or non-infectious (60%) indications, were analysed over a mean of 3.37 (±2.29) years. A total of 3426 leads were extracted; and, overall, 95% full procedural, 4% partial procedural, and 98% clinical success were demonstrated. Within the patient cohort, 1.8% (37/2049) experienced major complications, with cardiac tamponade being predominant (30/37). Cardiac tamponade was identified as the main cause of mortality, as well as the cause of all procedure-related deaths (6/2049; 0.3%). Cardiac tamponade occurred in 1.8% of atrial and 0.3% of right ventricular lead extractions, with fatal tamponade reported in 9% of atrial, 40% of ventricular, and 67% of coronary sinus lead extractions. No association between lead location and cardiac tamponade-related mortality was observed; however, lead location did affect the success of pericardiocentesis. The cardiac tamponade-related mortality rate was 37% when TLE was performed in an electrophysiology laboratory. No deaths were reported when the procedure was performed in a cardiac surgery or hybrid operating room. Long-term survival was improved when TLE was performed due to non-infectious indications, rather than pocket infection or lead-related endocarditis ( P  < 0.001). Conclusion: Using conventional non-powered mechanical sheaths, TLE was effective even in patients at high risk of complications.